CRITICAL REVIEW OF ANTIBIOTIC STEWARDSHIP PROGRAMS AND EVALUATING STRATEGIES FOR COMBATTING ANTIMICROBIAL RESISTANCE AND IMPROVING PATIENT SAFETY - 1Hussain Saleh Alsharmah, 2Yahya Ali Saleh Alyami, 3Hamed Mana Ali Al Mordef, 4Ahmed Mohammed Alshareef, 5Abdullah Hassan Mohmad Almoyed, 6Gassim Hassan Mohammed Almoyed, 7Amer Mohammed Mohammed, 8Hadi Ali Klfoot, (Chelonian Research Foundation, 2022)
Anti-microbial resistance (AMR) poses a significant danger to worldwide well-being, and successful anti-microbial resistance administrations (ASPs) are required to relieve its effects. This article gives a basic audit of ASPs, analyzing their techniques, adequacy, and challenges in combating AMR and making strides in patient security. A comprehensive writing survey assesses different perspectives of ASP, counting its utilization, results, and effect on antiretroviral hones. Strategies and approaches for measuring ASP are talked about. Comes about and discoveries are upheld by charts, tables, and charts highlighting the part of ASPs in tending to AMR and progressing patient security. The dialog investigates the effect of ASP on wellbeing rules, inoculation hones, and AMR administration, whereas the conclusion gives suggestions for creating ASP that will advantage AMR. Keywords: Antibiotic stewardship programs, antimicrobial resistance, patient safety, antimicrobial prescribing, healthcare delivery.